Ultrasound and Microwave Coassisted Synthesis and Luminescent Properties of (Ln = La, Gd; ) Phosphors - Jing Hu; Qianming Wang (Journal of Chemistry)
In order to control reaction temperature and reduce processing time, a new method of ultrasound irradiation with microwave heating was used to synthesize (Ln = La, Gd; ) phosphors at only 80°C in 30 minutes. Their crystal structures and morphologies which have been verified by X-ray diffraction (XRD) and scanning electron microscopy (SEM) exhibited gradual changes due to the insertion of lanthanide ions (La or Gd) in calcium molybdates. Codoping of lanthanum ions () would enhance the emission intensities that were supported by fluorescent spectrophotometry (FL).